PENGARUH KETIMPANGAN PENDAPATAN DAN PERTUMBUHAN EKSPOR TERHADAP EMISI CO2 DI INDONESIA - Ulfa, Nadia; Ichsan, Ichsan (Jurnal Ekonomi Regional Unimal, 2024)
This research aims to determine the effect of income inequality, and export growth on CO2 Emissions in Indonesia. This research uses secondary data from 1990-2021 obtained from the World Bank. The data analysis model uses a Autoregressive Distributed Lag (ARDL) analysis. The research results show that in the short term income inequality has a negative and significant effect on CO2 Emissions in Indonesia, while in the long term income inequality has a positive and insignificant effect on Indonesia's CO2 Emissions. Export growth in the short term has a positive and significant effect on Indonesia's CO2 emissions, while in the long term export growth has a positive and insignificant effect on CO2 emissions in Indonesia.